1974
DOI: 10.1017/s0043174500037036
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of Picloram by Soil Microorganisms: A Proposed Reaction Sequence

Abstract: The 6-hydroxy derivative of picloram (4-amino-3,5,6-trichloropicolinic acid) is not on the main pathway of the soil microbial decomposition sequence for picloram. Rather it may be formed in very small amounts in a competing reaction. Decarboxylation of picloram cannot be the initial reaction in this sequence and, in fact, does not occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…The results from the degradation study clearly show that degradation of DCP occurred mainly by microbial means, as was also shown to be the case for picloram degradation (National Research Council, 1974). The lack of metabolite accumulation (particularly the 6-hydroxy derivative) also confirms the hypothesis of Meikle et al (1974), that the rate-limiting step in the degradation sequence of picloram is a ring cleavage and a prior hydroxylation at the 6 position is not involved. The slow degradation rate in the soil-amended culture medium over a period of 96 days was unexpected as was the lack of significant microbial activity.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The results from the degradation study clearly show that degradation of DCP occurred mainly by microbial means, as was also shown to be the case for picloram degradation (National Research Council, 1974). The lack of metabolite accumulation (particularly the 6-hydroxy derivative) also confirms the hypothesis of Meikle et al (1974), that the rate-limiting step in the degradation sequence of picloram is a ring cleavage and a prior hydroxylation at the 6 position is not involved. The slow degradation rate in the soil-amended culture medium over a period of 96 days was unexpected as was the lack of significant microbial activity.…”
Section: Discussionsupporting
confidence: 78%
“…Upon subsequent methylation in 10 % methanol/ chloroform solution of the acidified hydrolysis product, the equilibrium mixture would become effectively fixed into its two isomeric forms giving the 6-methoxy and the iV-methyl, 6-keto derivatives of DCP. Thus, even though it may be possible to favor the isolation of a 6-hydroxy derivative by careful choice of work-up conditions as was done for picloram by Meikle et al (1974), it would appear that any subsequent redissolving and methylation of the product would lead to a mixture of isomeric forms. Hence care must be taken to look for both possible products in any methylation/GLC method of determining degradation products of picloram type herbicides.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of the culture began to level-off around days 4 and 5, and this corresponded to the complete degradation of the picloram within the culture medium. While other microorganisms have been reported to degrade picloram, degradation has been found to be slow and incomplete (8,9,13,15). Moreover, while the yeast Rhodotorula glutinis has previously been reported to partially degrade picloram after extensive (1 month) incubation (15 ), to our knowledge, this is the first report of a pure yeast culture that has the ability to rapidly degrade this herbicide in a few days.…”
Section: Resultsmentioning
confidence: 99%
“…These authors reported that picloram was only partially degraded to an isomer of dichloro-4-amino-2-pyridinecarboxylic acid following 50 days of acclimation and a 30 day incubation period, and then after another 90 days of incubation, another unknown metabolite accumulated. In general, microbial degradation of picloram has been found to be relatively slow and often incomplete ,,, . While the exact mechanism(s) by which microorganisms degrade picloram is unknown , Meikle et al proposed that degradation in soil is initiated by an oxygen-requiring ring-cleavage dioxygenase.…”
Section: Introductionmentioning
confidence: 99%
“…Large halogens such as chlorine can block the metabolism of pyridine derivatives by the maleamate pathway [16]. Meikle et al [17] reported the accumulation of a 6-hydroxy derivative of picloram (4-amino-3,5,6-trichloropicolinic acid) in soil, but kinetic discrepancies suggested that the compound is not a major metabolite.…”
Section: Introductionmentioning
confidence: 99%